The Impact of CO2 and Climate State on Whether Dansgaard–Oeschger Type Oscillations Occur in Climate Models - Irene Malmierca‐Vallet; Louise C. Sime; Paul J. Valdes; Marlene Klockmann; Guido Vettoretti; John Slattery (Geophysical Research Letters)
Abstract Greenland ice core records feature Dansgaard–Oeschger (D‐O) events, which are abrupt warming episodes followed by gradual cooling during ice age climate. The three climate models used in this study (CCSM4, MPI‐ESM, and HadCM3) show spontaneous self‐sustained D‐O‐like oscillations (albeit with differences in amplitude, duration, and shape) in a remarkably similar, narrow window of carbon dioxide (CO2) concentration, roughly 185–230 ppm. This range matches atmospheric CO2 during Marine Isotopic Stage 3 (MIS 3: between 27.8 and 59.4 thousand of years BP, hereafter ka), a period when D‐O events were most frequent. Insights from the three climate models point to North Atlantic (NA) sea‐ice coverage as a key ingredient behind D‐O type oscillations, which acts as a “tipping element.” Other climate state properties such as Mean Atlantic Meridional Overturning Circulation strength, global mean temperature and salinity gradient in the Atlantic Ocean do not determine whether D‐O type behavior can occur in all three models.